Analisis Yuridis Perlindungan Hukum Perjanjian Dibawah Tangan Berdasarkan Putusan Pengadilan No.161/pdt.g/2011/pn-mdn. (Studi Kasus PT Merim Property dan Cv Rira Karya) - Weriyus Heston Marbun (Universitas Islam Sumatera Utara, 2020)
Legal protection for every Indonesian citizens without exception can be found in the 1945 Constitution of the Republic of Indonesia (1945 Constitution), therefore every product produced by the legislature must always be able to provide guarantees of legal protection for all people, even they must be able to capture legal and justice aspirations that develop in society. In the Civil Code article 1233 states,